Entrenamiento de la fuerza con el método de oclusión vascular en estudiantes de ciencias del deporte (2018)
In order to establish the efects of a six-weeks strength training program with vascular occlusion from the arm muscle, first-semester university students, who worked in a two session weekly basis, with loads of 30% of repetition (MRI), performing two exercises for the biceps and triceps muscular groups, using a tensiometer with a pressure of 100 millimeters of mercury (mmHg). The study was framed within the quantitative, experimental, cross-sectional approach, two measurements were made, at the beginning and at the end of the study, they were carried out with previous signed informed consent. The sample in males (n = 20), 19.5 ± 1.50 years, for the variables of the right bicipital fold was between 5 ± 1.22 mm (mm) and 4.34 ± 1.10 mm and left 4.8 ± 2.39 mm and 4.26 ± 2. 07 mm, where the right perimeter extended 27.57 ± 2.33 cm (cm) and 28.80 ± 2.45 cm and the left 27.32 ± 2.42 cm and 28.36 ± 2.45 cm, the right relaxed perimeter 28.48 ± 2.47 cm and 29.96 cm ± 2.37 cm, the left 28.17 ± 2.51 cm and 29, 50 ± 2.46 cm and the right contracted perimeter 29.75 ± 2.78 cm and 31.66 ± 2.57 cm the left 29.26 ± 2.75 cm and 31.22 ± 2.51 cm. As for biceps curl alternating exercises hammer with dumbbell 22.98 ± 8.58 kilograms (kg) and 28.42 ± 9.79 kg, French flat bench press 21.11 ± 7.67 kg and 25, 75 ± 7.50 kg. The most outstanding results in the reduction of the bicipital fold, the increase of the perimeters of the relaxed arm, contracted and the increase of the maximum repetition in two exercises are evidenced.